Exploring case-based reasoning for web hypermedia project cost estimation. (25th July 2005) - Mendes, Emilia; Mosley, Nile; Counsell, Steve
This paper compares several methods of analogy-based effort estimation, including the use of adaptation rules as a contributing factor to better estimation accuracy. Two data sets are used in the analysis. Results show that best predictions were obtained for the dataset that presented a continuous 'cost' function and was more 'unspoiled'.